Identification of new celiac disease autoantigens using proteomic analysis - Stulík, Jirí; Hernychová, Lenka; Porkertová, Stanislava; Pozler, Oldrich; Tucková, Ludmila; Sánchez, Daniel; Bures, Jan (Proteomics, 2003)
Celiac disease is an autoimmune disorder in which gluten peptides presented by specific HLA-DQ2- and HLA-DQ8-positive antigen presenting cells elicit immune response in connective tissue of lamina propria. Immunoglobulin A (IgA) antiendomysial antibodies are specific for celiac disease and are used for screening, diagnosis and follow-up of this disease with an almost 100% sensitivity and specificity. The major target antigen of IgA antiendomysial antibodies was identified as tissue transglutaminase; nevertheless, the existence of the additional unique celiac disease-specific autoantigens is anticipated. In this study we have utilized a proteomic approach in order to search out new autoantigens recognized by serum antibodies of patients with active celiac disease. We report the detection of 11 proteins that were immunorecognized with various frequencies by sera of patients with celiac disease. Four autoantigens were identified by mass fingerprinting approach as actin, ATP synthase beta chain and two charge variants of enolase alpha. While production of IgA antibodies against actin molecules were described earlier, the existence of autoantibodies to ATP synthase beta chain and enolase alpha species in sera collected from patients with active celiac disease are described for the first time. These results are suggestive of the existence of additional celiac disease autoantigens with possible diagnostic utility.
Keywords: Celiac Disease; Autoantibodies; proteom; Child; 2D gelová elektroforéza; HLA-DQ Antigens; HLA-DQ antigeny; dítě; Adult; Electrophoresis, Gel, Two-Dimensional; dospělí; Mass Spectrometry; celiakie; Autoantigens; autoantigeny; proteomika; lidé; fosfopyruváthydratasa; Humans; autoprotilátky; Phosphopyruvate Hydratase; imunoglobulin A; hmotnostní spektrometrie; Proteomics; Immunoglobulin A; Proteome